Dinamika Interaksi Teman Sebaya Berdasarkan Kapasitas Regulasi Emosi di Panti Sosial Anak - A. Nurhidayah. M; Maya Maulida; Nopi Armadani; Abdul Riski Saputra; Rini Fitriani Permatasari (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
This study aims to examine the dynamics of peer interaction based on the emotional regulation capacity of children and adolescents living at Dharma Child Protection Social Institution in Samarinda. This research employed a descriptive qualitative approach involving four children and adolescents and two caregivers. Data were collected through interviews, observations, and documentation and analyzed using the Miles and Huberman model. The findings indicate that emotional regulation capacity influences how children and adolescents interact with their peers. Some participants tended to suppress emotions and avoid conflict, while others expressed emotions openly. Conflicts generally arose from differences in personality, violations of personal boundaries, and verbal bullying. Nevertheless, positive peer relationships remained an important source of social and emotional support. These findings highlight the importance of developing emotional regulation skills to promote healthy social interactions within social care institutions.